AS NANOCÁPSULAS CONTENDO MELOXICAM APRESENTAM EFEITO ANTINOCICEPTIVO MAIS PROLONGADO QUE O FÁRMACO NA FORMA LIVRE EM CAMUNDONGOS - Villalba, Benonio Terra (2011)
The present study investigated the time-course of antinociceptive effect of meloxicam-loaded nanocapsules (M-NC) (5 mg/kg, intragastrically (i.g.) in chemical and thermal models of pain in mice. The antinociceptive activity of M-NC was compared to free meloxicam (M-F) (5 mg/kg, i.g.). Experiments were carried out in male Swiss mice previously treated with M-NC or M-F or suspension without drug (B-MC), at different times (0.5 – 120 h). M-NC elicited a significant increase in the tail-immersion and hot-plate response latency and this effect remained significant up to 24 h. Antinociceptive action of M-NC in the thermal test was similar to M-F. M-NC reduced the acetic acid-induced abdominal writhing up to 48 h, while M-F produced an inhibition to 24 h. Pre-treatment up to 96 h with M-NC produced a marked reduction of the licking time in the first and second phases in the formalin test, while M-F had significant effect against the duration of licking up to 24 h in the first phase and at 0.5 h in the second phase. Paw oedema formation induced by formalin was reduced up to 96 h of pre-treatment with M-NC, while M-F had no significant effect against the formation of the paw oedema. Pre-treatment of up to 72 h with M-NC produced a marked reduction of the licking time and paw oedema formation induced by glutamate, while M-F had significant effect in both parameters up to 24 h. The antiedematogenic effect of M-NC remained significant up to 96 h after the administration, while M-F produced an inhibition of ear oedema up to 24 h. In conclusion, time-curse of antinociceptive effect indicated that M-NC exhibited more prolonged action than M-F. Thus, M-NC may be of potential interest in developing new prolongated delivery systems for the treatment of pain.